Blockchain Distributed Cloud Storage Network Tool(BCCNT) - Sharma, Ankita; Bansal, Rishabh; Soren, Nimish Niret (International Journal of Computer Sciences and Engineering, 2018)
BCCNT (Blockchain Cloud Network Tool) is open source project to make cloud storage applications decentralized which will make them secure and efficient for the end users. It provides a platform for the prototype of a completely distributed network. It is proposed to develop an application which can provide a user interface for less technical/non-technical users. The cryptocurrencies functions both as a bonus and payment method. While on the other hand a separate blockchain is used to store the data for the metadata file. The application needs to be run in a P2P mesh from systems that will execute the code, present on a public chain of data instead of a central database. The main thought behind BCCNT is to offer a group of functions which makes it easy to connect Cloud & major platforms’ and end users.